1978
DOI: 10.1203/00006450-197804001-00926
|View full text |Cite
|
Sign up to set email alerts
|

921 Renal Abnormalities in Fetal Alcohol Syndrome

Abstract: nd conoenital anomalies 43% greater (P<.02) in offspring of 2 -s than of nonsmokers. 46,865 placentas were available i n which maternal smoking i s t o r i e s had ,been recorded. Abnormalities i n these placentas rovide plausible explanations f o r most of the excess f e t a l and eonatal mortality associated with cigarette smoking. The placentas o f the cigarette smokers had a number of structural abiormali t i e s characteristic of reduced maternal perfusion, includ ing o b l i t e r a t i v e e n d a r t e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Genitourinary malformations have been described as occurring more commonly in children with FAS than in general (Clarren and Smith 1978; Havers et al 1980; Qazi et al 1979). A few animal studies have found that fetal alcohol exposure may result in abnormalities of the genitourinary tract (Gage and Sulik 1991; Randall et al 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Genitourinary malformations have been described as occurring more commonly in children with FAS than in general (Clarren and Smith 1978; Havers et al 1980; Qazi et al 1979). A few animal studies have found that fetal alcohol exposure may result in abnormalities of the genitourinary tract (Gage and Sulik 1991; Randall et al 1977).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, renal hypodysplasia is caused by salt loading during embryonic development in bradykinin B2 receptordeficient, but not in wild-type, mice [88]. Exposure to cocaine or alcohol during gestation results in CAKUT in children [92,93]. Importantly, the mechanistic basis for CAKUT associated with altered intrauterine environment remains to be elucidated.…”
Section: Insights Into the Mechanisms Controlling Cakut Phenotypementioning
confidence: 94%
“…Human studies have demonstrated that infants exposed to cocaine in utero had an increased risk of renal tract anomalies including renal hypoplasia (84 -86). Similarly, infants with Fetal Alcohol Syndrome also have a higher incidence of renal malformations, including small kidneys (87)(88)(89), and a recent study in sheep demonstrated that repeated alcohol exposure in late gestation leads to a mild nephron deficiency (90). Several clinical medications have also proven detrimental to fetal nephron endowment.…”
Section: In Utero Environment and Renal Hypoplasiamentioning
confidence: 99%